EJMM 2021
DOI: 10.51429/ejmm30121
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23/ Interleukin -17 Axis in Chronic Spontaneous Urticaria: A Case- Control Study

Abstract: Background: Chronic Spontaneous Urticaria (CSU) is a common health problem and its clear etiology is not established yet. Several theories have been tried to illustrate its etiology and pathogenesis. Autoantibodies and inflammatory cytokines like IL-23 and IL17 are hypothesized to take part in CSU pathogenesis and outcome. Objectives: To detect serum levels of IL-23 and IL-17A among CSU patients and to determine its correlation with disease severity and its relation to autoreactivity. Methodology: Serum levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our analysis showed significantly lower IL-23 levels in AU and CU patients with respect to CG. Different results were obtained in several papers on CU [ 3 , 4 , 20 ], where additionally a correlation between IL-23 levels and CU severity was shown [ 4 ]. On the other hand, Degirmenci et al reported lower levels of IL-17 and IL-23 in patients with CU, which was explained by the effect of cytokine consumption during the ongoing inflammatory process [ 8 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our analysis showed significantly lower IL-23 levels in AU and CU patients with respect to CG. Different results were obtained in several papers on CU [ 3 , 4 , 20 ], where additionally a correlation between IL-23 levels and CU severity was shown [ 4 ]. On the other hand, Degirmenci et al reported lower levels of IL-17 and IL-23 in patients with CU, which was explained by the effect of cytokine consumption during the ongoing inflammatory process [ 8 ].…”
Section: Discussionmentioning
confidence: 93%
“…So far, most reports, like our work have shown higher IL-17 levels in CU patients [ 3 , 9 ] compared to CG. Additionally, this increase was found in patients with CU and a positive autologous serum skin test (ASST) [ 20 ]. Atwa et al reported a correlation between IL-17 levels and urticaria severity [ 21 ], which was not confirmed by Chen et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed signi cantly lower IL-23 levels in AU and CU patients with respect to CG. Different results were obtained in several papers on CU [3,4,20], where additionally a correlation between IL-23 levels and CU severity was shown [4]. On the other hand, Degirmenci et al reported lower levels of IL-17 and IL-23 in patients with CU, which was explained by the effect of cytokine consumption during the ongoing in ammatory process [8].…”
Section: Discussionmentioning
confidence: 93%
“…So far, most reports, like our work have shown higher IL-17 levels in CU patients [3,9] compared to CG. Additionally, this increase was found in patients with CU and a positive autologous serum skin test (ASST) [20]. Atwa et al reported a correlation between IL-17 levels and urticaria severity [21], which was not con rmed by Chen et al [4].…”
Section: Discussionmentioning
confidence: 95%